2021
DOI: 10.1055/s-0040-1722269
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Usefulness of YouTube Videos Related to Endoscopic Transsphenoidal Surgery for Patient Information

Abstract: Objectives This article evaluates the completeness and accuracy of YouTube videos related to endoscopic transsphenoidal surgery (ETS) as a source for patient information. Design YouTube was searched using relevant terms pertaining to ETS. Videos were evaluated independently by two physician reviewers experienced in ETS. Video demographics including uploader source along with validity scores based on predetermined checklists were captured. Setting Internet. Participants Not applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…5 A study evaluating YouTube videos related to endoscopic transsphenoidal surgery showed that videos with higher VPI and videos with higher view counts were not significantly associated with higher scores for DISCERN criteria or JAMA score. 24 They determined patients may be obtain-ing information from lower quality and less reliable videos rather than high-quality videos with relatively lower VPI. Therefore, users seeking out surgical video resources must be wary of videos deemed popular by conventional metrics because they may not contain the highest-quality or most reliable information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A study evaluating YouTube videos related to endoscopic transsphenoidal surgery showed that videos with higher VPI and videos with higher view counts were not significantly associated with higher scores for DISCERN criteria or JAMA score. 24 They determined patients may be obtain-ing information from lower quality and less reliable videos rather than high-quality videos with relatively lower VPI. Therefore, users seeking out surgical video resources must be wary of videos deemed popular by conventional metrics because they may not contain the highest-quality or most reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as noted by Levin et al, lay people may confuse high view counts for videos of high quality. 24 One of the few significant metric differences between videos uploaded by academicaffiliated users and independent users is the amount of time the video has been available for public access. When initially evaluated, videos uploaded by independent users were on YouTube for 2521.42 ± 1297.95 days compared with 1174.88 ± 943.12 days (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A study that set out to estimate the prevalence of poor reading skills in the OHNS outpatient population in the United Kingdom found that 28% of their patients had poor reading skills and were unable to comprehend medical leaflets 42 . Moreover, studies on the utilization of Internet videos and websites for OHNS procedures have concluded they are of poor quality and difficult for patients to comprehend, making national society websites the ideal source for trusted patient education material 43–46 . This requires OHNS societies to provide accurate information, written at a comprehensible level, as these are viewed as trusted sources of information for patient education 29 …”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, studies on the utilization of Internet videos and websites for OHNS procedures have concluded they are of poor quality and difficult for patients to comprehend, making national society websites the ideal source for trusted patient education material. [43][44][45][46] This requires OHNS societies to provide accurate information, written at a comprehensible level, as these are viewed as trusted sources of information for patient education. 29 Our study concluded that neither AAO-HNS, CSOHNS, nor ENT UK had online patient materials written at a sixthgrade reading level as recommended by the AMA.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were adapted and modified from previous studies [12,13]. Videos made in English, French, Arabic, Swahili and Hausa will be included.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%